A nightmare on Elm Street [videorecording (DVD)] - Craven, Wes; Saxon, John, 1935-2020-; Blakley, Ronee; Langenkamp, Heather, 1964-; Depp, Johnny (Infinifilm., 1999)
When her best friend Tina is brutally murdered, teenager Nancy suspects the killer isn't Tina's boyfriend but rather a much more horrifying figure from her dreams. Convinced that this vicious murderer is stalking her friends and killing them as they sleep, Nancy enters a desperate race against time to bring him out of her dream world and stop the bloodbath ... before she falls asleep and becomes his next victim.